The Morphology of Flutes - Pett, John (My University, 1970)
Measurements were taken on 1511 flutes from various localities in Eastern North America. Over 85% of the flutes recorded are from the Cloridorme Formation (Ordovician) of North-Eastern Quebec. Flutes occur in a variety of shapes, on A, B and C beds of the Bouma sequence, but no one shape is confined to any one bed type. However, A beds do tend to have a larger proportion of wide flutes on their soles than B or C beds. Whilst flutes on B and C beds are often found associated with brushes, grooves and signs of organic activity, those on A beds are rarely found associated with any other sole marks.
Several parameters of width, length and depth have been measured, but the maximum length of the flute was shown to be an inconsistently measurable parameter. by means of an operator error experiment. The maximum -depth of the flute is found to be independent both of the bed type on which it occurs and also the maximum grain size of that bed. No relationship is found between the total bed thickness and the maximum grain size of the bed.
As flutes become broader, the point of maximum depth is found to migrate downstream so that wider flutes have their point of maximum depth quite far back from the nose.
Factor analysis shows that two factors control the overall morphology of the flutes: firstly the shape of the nose portion, in planview termed the 'nose angle': and secondly, the ratio of the maximum depth and the distance of this point from the nose.
Calculations based on previous experimental work, but using field measurements, suggest that velocities in the order of 7 metres/sec and 4 metres/sec are required for the continuance of flutes on B and C beds respectively.
Keywords: morphology; flutes; Cloridorme Formation